2010
DOI: 10.1002/jbm.a.32993
|View full text |Cite
|
Sign up to set email alerts
|

Role of thiol‐complex formation in 2‐hydroxyethyl‐ methacrylate‐induced toxicity in vitro

Abstract: Methacrylate monomers that are found to leach from cured resin-based dental materials induce biological effects in vitro. The underlying mechanisms have not been fully elucidated although involvement of increased cellular reactive oxygen species (ROS) and DNA-damage has been suggested. In this in vitro study we have elucidated the impact of a commonly used methacrylate monomer, HEMA, on the level and oxidation state of cellular glutathione, intracellular ROS level, as well as the formation of complex between H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…In contrast to catalase and Prxd1 expression, levels of GPx1/2 decreased in cultures exposed to HEMA. Yet, the present findings support our recent model which indicates that the inhibition of GPx1/2 expression in the presence of HEMA is a result of GSH depletion, most likely caused by the adduct formation of GSH with resin monomers [17,35,42]. OTC or NAC, both of which supply cysteine for GSH synthesis, may increase or maintain GPx1/2 expression at relatively high levels, while the same effect is caused by BSO alone via the induction of high levels of H 2 O 2 after GSH depletion [17].…”
Section: Expression Of Nrf2 In Hema-exposed Mouse Macrophagessupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast to catalase and Prxd1 expression, levels of GPx1/2 decreased in cultures exposed to HEMA. Yet, the present findings support our recent model which indicates that the inhibition of GPx1/2 expression in the presence of HEMA is a result of GSH depletion, most likely caused by the adduct formation of GSH with resin monomers [17,35,42]. OTC or NAC, both of which supply cysteine for GSH synthesis, may increase or maintain GPx1/2 expression at relatively high levels, while the same effect is caused by BSO alone via the induction of high levels of H 2 O 2 after GSH depletion [17].…”
Section: Expression Of Nrf2 In Hema-exposed Mouse Macrophagessupporting
confidence: 76%
“…The crucial role of the non-enzymatic antioxidant glutathione (GSH) for the generation of oxidative stress in monomer-exposed cell cultures has been previously revealed [17,35,36]. Here we hypothesized that an unambiguous influence of GSH on the formation of a specific type of ROS not investigated so far might lead to specific therapeutic options.…”
Section: Fl-2 (Propidiummentioning
confidence: 92%
“…Methacrylate toxicity has been studied in several different cell lines. Based on similarities among many of the studies, a general mechanism could be postulated for the onset of methacrylate toxicity including GSH depletion and increased level of cellular ROS 23, 28–31. One major drawback of these studies is the reported reduction of phase I metabolic capacity in cell lines compared with cells in vivo and unpassaged primary cultures 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cultures were exposed to various concentrations of HEMA (0.5–2 m M ) for up to 2 h. Glutathione (GSH) concentrations were determined by flow cytometry as previously described 23. Briefly, cells were incubated with 50 μ M monobromobimane (MBrB; Sigma‐Aldrich, St. Louis, MO) in PBS for 30 min after trypsinization.…”
Section: Methodsmentioning
confidence: 99%
“…N-acetylcysteine, a precursor of GSH, and antioxidant vitamins have been reported to antagonize the cytotoxic activity of resin monomers, 10,11 implying the involvement of oxidative stress in cell death. Recently, formation of a chemical complex between GSH and methacrylate was revealed, 12,13 which may explain how TEGDMA and HEMA deplete GSH. Together, the results of these various studies indicate that oxidative stress is responsible for resin monomer-induced cell death.…”
Section: Introductionmentioning
confidence: 99%